Long-term Health Outcomes in Survivors of Childhood Cancer Diagnosed Between 1990 and 2000 in a Large US Integrated Health Care System. Issue 2 (March 2016) - Chao, Chun; Xu, Lanfang; Bell, Elizabeth; Cooper, Roberto; Mueller, Lisa
Abstract : We evaluated the long-term health outcomes of childhood cancer survivors (CCS) using data from the Kaiser Permanente Southern California (KPSC) health plan, whose members have similar health care coverage. Five-year survivors of invasive cancer diagnosed at ages 0 to 18 years between 1990 and 2000 at KPSC were identified and followed to December 31, 2010. A group of KPSC members without history of cancer were 10:1 matched to each CCS for comparison. Health outcomes of interest included mortality, second cancer, and chronic comorbidities. Incidence rate ratio (IRR) was estimated using multivariable Poisson regression. Cumulative incidence of each health condition over time was calculated. A total of 652 CCS and 6520 noncancer subjects were included. Compared with the noncancer subjects, IRR was significantly elevated among CCS for mortality (IRR=14.1), second cancer (IRR=10.0), cerebrovascular disease (IRR=10.1), dyslipidemia (IRR=1.9), hearing/vision loss (IRR=5.1), heart disease (IRR=3.9), hypogonadism (IRR=4.2), renal failure (IRR=13.4), and thyroid disorder (IRR=6.4). Approximately 40% of CCS developed at least 1 chronic health condition within 15 years of cancer diagnosis. Cumulative incidence curves showed different risk trajectories of various comorbidities which may inform screening schedule. These data suggested that CCS treated in a more contemporary era continued to experience substantial disease burden in their adolescent and young adulthood. Abstract : Supplemental Digital Content is available in the text.